Inventory Management Through Information Systems Design and Warehouse Layout in Sans Boxer - Isman Budiman; Siti Samsiyah Purwaningsih (Records Management System Journal, 2023)
Inventory management is a crucial aspect in the business world. To achieve effective inventory management, a proper inventory information system is need. However, many companies, especially SMEs, still rely on conventional inventory management systems. Additionally, the layoutof storage also affects inventory control. The right layout can improve work efficiency and space utilization. Sans Boxer, an SME company engaged in clothing, faces ssues in inventory control. Some problems encountered include unrecorded transaction, innacurate stock information, limited storage, capacity, and difficulties in storing and retrieving items. To address these probles, a project was created for an inventory information and the design on storage layout. The inventory information system was develop as a Microsoft Access application designed using the PIECES method. Meanwhile, the sotrage layout was designed using the Shared Storage method, considering the available space for optimal utilization. This project resulted in an inventory information system based on Microsoft Access and a design for the storage layout. Based on the inventory system’s testing results, improvements were observed in inventory control, including enhanced employee performance, easier access to information, reduced inventory costs, better control, improved work efficiency, and enhanced customer service.The proposed storage layout design can increase the storage capacity to 4500 pcs, compared to the initial capacity of 1500 pcs.